I12 The role of the cerebellum in juvenile huntington's disease (JHD). (13th September 2016) - Nopoulos, Peggy; Lee, Jessica; Epping, Eric; Martin, Erin; Mathews, Kathy; Espe-Pfeiffer, Patricia; Magnotta, Vincent
Abstract : Background: The cerebellum is integrated structurally and functionally with the striatum with the anterior lobe having input into the indirect pathway of the striatum – the pathway responsible for movement inhibition, and the pathway affected most by HD. In JHD, hyper-connectivity of the cerebellum could lead to the hypokinetic state seen in JHD. Aim: To evaluate brain structure in a sample of JHD subjects Methods: The University of Iowa Kids-JHD program enrols children 8–18 years of age who have already received the clinical diagnosis. Each child undergoes an MRI scan. A total of 10 children with JHD, ages 6–17 were studied (mean CAG = 77). JHD subjects were compared to a large data base (>200 subjects) of control children. Structural brain measures and DTI measures were evaluated between groups. Results: Subjects with JHD had substantially reduced Intracranial Volumes (ICV). After controlling for the overall small size of the brain, JHD, the striatum and globus pallidus were specifically affected with volumes that were far below normal. Thalamus and hippocampus were of normal size. The cerebellum was enlarged in the JHD sample. DTI measures indicated a hyper-connectivity between the cerebellum and the striatum. Finally, the size of the cerebellum and the strength of the associated white matter tracts were directly related to abnormalities in motor function (large volume and high FA associated with worse motor scores). This suggests that the enlargement and hyper-connected cerebellum is driving the hypokinetic state in the JHD subjects. Conclusion: HTT is vital for normal brain development. In its mutant form, mHTT may alter the development of the striatum which in turn spurs the development of the cerebellum to have greater input to the indirect pathway. In AOHD this is likely compensatory. However in JHD, the striatal development is so severe that the cerebellar compensation is driven so far that instead of facilitating function, it actually inhibits motor function, manifesting in the hypokinetic state of JHD.